(untitled) - O'leary, Timothy J. (New York, 2011)
Office 2010: A Case Approach offers running case study throughout the text to help students understand the material in a consistent, relevant environment. Through this theme of “Making Office Relevant,” this text helps students understand why they need this course and these skills. Student success is assured through clear step-by-step instruction, plentiful screen captures and conceptual explanations
Keywords: Microsoft Access,Database management,Quản lý cơ sở dữ liệu,Phần mềm Access